Mainstream wastewater treatment by polyaluminium ferric chloride (PAFC) flocculation and nitritation-denitritation membrane aerated biofilm reactor (MABR). (April 2023) - Li, Ming; Liu, Longzhi; Sun, Zhiye; Hu, Boyang; Li, Xinglin; Lan, Meichao; Guo, Hong; Li, Baoan
Abstract: To reduce the carbon emission of sewage treatment, a novel adsorption-biodegradation (A-B) process, flocculation pretreatment as A-stage and nitritation-denitritation MABR as B-stage, was proposed in the study. It was found that 27.37 %–49.69 % of organics can be removed from actual wastewater by flocculation with polyaluminium ferric chloride (PAFC). The pretreated wastewater could be further treated by nitritation-denitritation MABR with low aeration pressure (2–5 kPa) without any extra organics. The NH4 + -N, total nitrogen (TN), and chemical oxygen demand (COD) removal efficiency can reach 100 %, 84.04 %, and 98.54 %, respectively. It was also found that the relative abundances of ammonia-oxidizing bacteria (AOB) (3.81 %–4.76 %) and denitrifying bacteria (DB) (4.30 %–5.59 %) were higher than that of nitrite-oxidizing bacteria (NOB) (2.08 %–2.39 %) in the MABR even after 130 days of operation according to the microorganism identification by 16S rRNA sequencing technology. This implied that low oxygen aeration in MABR can prevent NOB from becoming dominant bacteria. Furthermore, it was found that there were indeed traces of anaerobic ammonia oxidation (Anammox) bacteria (0.04 %–0.08 %) and were closely surrounded by other microorganisms in the MABR based on fluorescence in situ hybridization (FISH) technology. In addition, the microbial nitrogen metabolism process in the MABR was further analyzed according to the Kyoto Encyclopedia of Genes and Genomes (KEGG). The promising mainstream A-B process proposed in this study was expected to achieve nitrogen removal with little carbon and energy consumption in wastewater treatment plants (WWTPs). Graphical abstract: Unlabelled Image Highlights: A novel A-B process was proposed for mainstream wastewater treatment. Nitritation-denitritation MABR was built to treat sewage after flocculation. Nitrate-to-nitrite transformation ratio in the MABR can reach 90.54 %. Successfully reducing the relative abundance of NOB in MABR